An investigation on the climate-responsive design strategies of vernacular dwellings in Khams. (15th August 2019) - Nie, Qian; Zhao, Shichen; Zhang, Qun; Liu, Peng; Yu, Zhuoyu
Abstract: Successful building design balances ambitious environmental requirements and residential comfort by considering the regional culture, economic level, natural environment, indoor thermal comfort and energy consumption. Taking dwellings as a case study, this paper examines the potential of improving indoor thermal comfort through field investigations of indoor environments in the Tibetan area. Settlement location and layout designs, combined with the natural environment, religious culture, synchronous optimization of structural seismic performance and enclosed structure, and a semi-open space setting making full use of passive solar energy technology, is a major strategy for climate-responsive design in Khams that also meets local economic levels and modern living needs. The results show that this strategy can achieve 5 h with air temperatures over 16.4 °C (from 12:30–17:30) in a comfortable thermal environment without the consumption of fossil energy, while in the evening, the thermal environment indicators in the major living space remain stable with low heat loss, indicating that an appropriate heat source from local bioenergy can achieve indoor thermal comfort. Overall, the dwellings in Khams with abundant solar energy and a lack of fossil energy are very well adapted to local climate conditions. Highlights: Khams with ethnic diversity, complex terrain and frequent earthquakes. Vernacular architecture in Khams holds environmental adaptability, economic applicability and Tibetan culture. The optimization of structural seismic performance and enclosure structures is synchronous. Solar energy utilization technology is a key to improve thermal comfort in Qinghai-Tibet Plateau.